Uji Aktivitas Antioksidan Teh Herbal Daun Melinjo (Gnetum Gnemon L.) Dengan Menggunakan Spektrofotometri Visibel - Syarifah Aulia; Rafita Yuniarti; Gabena Indrayani Dalimunthe; Ridwanto Ridwanto (Institut Nalanda, 2023)
Antioxidants are compounds that can counteract / reduce the negative effects of free radicals that cause damage to the body. Natural antioxidants are used as an alternative in an effort to minimize the use of synthetic antioxidants which can cause carcinogens. Utilization of melinjo leaves as herbal tea is one effort to use natural antioxidants to minimize the use of synthetic antioxidants which can cause carcinogens. The purpose of this study was to determine the content of secondary metabolites contained in melinjo leaf tea, the characteristics of melinjo leaf tea and the antioxidant activity of melinjo leaf tea. This research was conducted by making melinjo leaf herbal tea through a drying process in a drying cabinet at 40oC, phytochemical screening, examining the characteristics of the tea, and testing the antioxidant activity. The results of the Phytochemical screening examination showed that melinjo leaf herbal tea contains alkaloids, flavonoids, saponins, tannins, steroids/triterpenoids. As well as having the characteristics of water content 5.6866%, water extract 36.9740%, total ash content 5.7658%, water soluble ash content to total ash 7.7066, acid insoluble ash content 0.54%. While the antioxidant activity test of melinjo leaf herbal tea showed very weak antioxidant activity with an IC50 value of 501.7622 ppm